Insurance Economic Growth Nexus: Evidence from a Small Open Economy - Orofuke, Patricia; Maku, Owen A. (Acta Universitatis Danubius. Œconomica, 2023)
Abstract: This study investigated the relationship between insurance and economic growth in Nigeria for the period 1998-2020. This study employed autoregressive distributed lag model (ARDL) estimation techniques in analyzing the data. Real Gross domestic product (RGDP) was used as proxy for economic growth while gross insurance premium (GIP), life insurance premium (LIP), non-life insurance premium (NLIP), human capital (HCAP), physical capital (PCAP), total insurance investment (TINV) and trade openness (OPEN) were used as proxies for insurance sector predictive variables. The result of the ARDL estimate revealed that the first lag of real gross domestic product (RGDP), non-life insurance premium (NLIP) and human capital (HCAP) were positively and statistically significant in explaining the variation in economic growth in Nigeria both in the shortrun and longrun. It is therefore recommended that Nigeria as a nation in seeking the welfare of its citizens must as a matter of priority, need to strengthen, build and develop a stable and vibrant insurance industry to foster all round economic growth and development. More, policies and programmes aimed at improving the quality of human capital such education, health entrepreneurial and skill acquisition should be pursued vigorously in Nigeria.